Design of split-capacitors applied in positive output super-lift luo-converters - Xiong, Yakun. (2011)
The voltage-lift technique is a common method used in electronics circuitry design to amplify output voltage. This technique overcomes the effects of parasitic elements effectively and increases the voltage transfer gain of DC/DC converters significantly. However, the output voltage increases in arithmetic progression stage by stage. The Super-Lift technique is more powerful than the VL technique; its voltage transfer gain can be a very large value. The SL technique implements the output voltage increasing in geometric progression stage by stage. This report will introduce a novel approach—SL technique armed by Split Capacitors that implement the output voltage increasing in higher geometric progression. Five newly designed series of Positive/Output SL Luo-Converters that armed with split capacitors will be listed below, including main series, additional series, enhanced series, re-enhanced series and multiple-enhanced series. In this report, both the theoretical analysis and simulation performances will be provided to verify the designed circuits.